Role of еlectromyography in assessing prognosis for children with obstetric brachial plexus injury in practice of a specialized center - M. L. Novikov; D. S. Druzhinin; V. A. Bulanova; T. E. Torno (Нервно-мышечные болезни)
The aim of current publication – to present our own experience in use of electromyographic examination in prognosis for children with obstetric brachial plexus injury to practical neurologists and neurophysiologists. Review of literature shows that common approaches to electrotrophysiological diagnosis of obstetric brachial plexus injury do not exist. The aim of this study– to evaluate retrospectively electrophysiological and sonographic parameters of obstetric brachial plexus injury in children, determining the most informative variables. Since 2007 to 2014 we examined 218 children, 74 of them were operated. Electrophysiological investigation in young children have difficulties in performance.We present our algorithm of diagnostic of obstetric brachial plexus injury: 1) testing main muscles, which perform basic movementsin upper limb (needle EMG of supra- and infraspinatus muscles and cutaneous EMG of biceps muscles); 2) localization of injury (paralysis or Duchenne – Erb palsy and electrophysiological criteria of spinal cord root avulsion). We found out that the most crucial role in assessing prognosis plays an examination of motor unit potentials (MUPs) duration. Absence of MUPs within needle EMG from supraspinatus muscle and absence of interference curve from biceps muscle during first 6 months have poor prognosis. After 6 months careful, dynamic study of MUPs duration in infraspinatus muscle and co-contraction of agonist and antagonist muscles is needed. To decide whether reconstructive surgery in a patient with obstetric brachial plexus injury is necessary, surgeon must analyze clinical and instrumental data. The possibility of usage of the ultrasonogrophy in brachial plexus injury requires further investigation.